Comment on" Topological quantum phase transitions of attractive spinless fermions in a honeycomb lattice" by Poletti D. et al - Corboz, Philippe; Capponi, Sylvain; Laeuchli, Andreas M; Bauer, Bela; Orus, Roman (2012)
In a recent letter [D. Poletti et al., EPL 93, 37008 (2011)] a model of attractive spinless fermions on the honeycomb lattice at half filling has been studied by mean-field theory, where distinct homogenous phases at rather large attraction strength , separated by (topological) phase transitions, have been predicted. In this comment we argue that without additional interactions the ground states in these phases are not stable against phase separation. We determine the onset of phase separation at half filling by means of infinite projected entangled-pair states (iPEPS) and exact diagonalization.